Making Experts: The Boundary Crossing of Knowledge and the Emergence of Relational Expertise in a School Makerspace - Jasmiina Leskinen; Kristiina Kumpulainen; Anu Kajamaa (MDPI AG, 2024)
Existing research has illuminated the multidimensional nature of knowledge creation in school makerspaces. Yet, limited research exists on the boundary crossing of knowledge in makerspaces and how it can lead to the emergence of relational expertise. Using video records of interactions between 10-13-year-old students and their teachers in a school makerspace, this ethnographic case study applied mediated discourse analysis to investigate the boundary crossing of knowledge and the emergence of relational expertise-i.e., engaging with one's own expertise, while recognizing, responding to, and building on others' expertise. The results demonstrate how relational expertise emerged through boundary crossing of knowledge, with increased opportunities for students to identify themselves as experts. The boundary crossing of knowledge was mediated by participating students and teachers as well as material objects, evidencing the social and material nature of relational expertise in the makerspace. By recognizing the makerspace as a boundary object and an epistemic tool, the study enhances current understanding of the boundary crossing of knowledge and the emergence of relational expertise within creative and digitally enhanced learning environments.